Generic pipelines using Docker : the DevOps guide to building reusable, platform agnostic CI/CD frameworks /: the DevOps guide to building reusable, platform agnostic CI/CD frameworks. ([2018]) - Atkinson, Brandon; Edwards, Dallas
No abstract available